Attributional and Relational Processing in Pigeons - Garlick, Dennis; Gant, Dana; Brakel, Linda A.; Blaisdell, Aaron P. (Frontiers in Psychology, 2011)
Six pigeons were trained using a matching-to-sample procedure where sample and rewarded comparisons matched on both attributional (color) and relational (horizontal or vertical orientation) dimensions. Probes then evaluated the pigeons’ preference to comparisons that varied in these dimensions. A strong preference was found for the attribute of color. The discrimination was not found to transfer to novel colors, however, suggesting that a general color rule had not been learned. Further, when color could not be used to guide responding, some influence of other attributional cues such as shape, but not relational cues, was found. We conclude that pigeons based their performance on attributional properties of but not on relational properties between elements in our matching-to-sample procedure.. Future studies should look at examining other attributes to compare attributional versus relational processing.